Adaptive dose painting for prostate cancer - Fredén, Emil; Tilly, David; Ahnesjö, Anders (Frontiers in Oncology, 2022)
Purpose: Dose painting (DP) is a radiation therapy (RT) strategy for patients with heterogeneous tumours delivering higher dose to radiation resistant regions and less to sensitive ones, thus aiming to maximize tumour control with limited side effects. The success of DP treatments is influenced by the spatial accuracy in dose delivery. Adaptive RT (ART) workflows can reduce the overall geometric dose delivery uncertainty. The purpose of this study is to dosimetrically compare ART and non-adaptive conventional RT workflows for delivery of DP prescriptions in the treatment of prostate cancer (PCa). Materials and Methods: We performed a planning and treatment simulation study of four study arms. Adaptive and conventional workflows were tested in combination with DP and homogenous dose. We used image data from 5 PCa patients that had been treated on the Elekta Unity MR linac; the patients had been imaged in treatment position before each treatment fraction (7 in total). We modelled the local radiation sensitivity from apparent diffusion coefficient maps of 15 high-risk PCa patients in a previous study; these maps were used as input for optimization of DP plans aiming for maximization of tumour control probability (TCP) under rectum dose constraints. A range of prostate doses were planned for the homogeneous arms. Adaptive plans were replanned based on the anatomy-of-the-day, whereas conventional plans were planned using a pre-treatment image and subsequently recalculated on the anatomy-of-the-day. The dose from 7 fractions was accumulated using dose mapping. The endpoints studied were the TCP and dose-volume histogram metrics for organs at risk. Results: Accumulated DP doses (adaptive and conventional) resulted in high TCP, between 96-99%. The largest difference between adaptive and conventional DP was 2.6 percentage points (in favour of adaptive DP). An analysis of the dose per fraction revealed substantial target misses for one patient in the conventional workflow that—if systematic—could jeopardize the TCP. Compared to homogeneous prescriptions with equal mean prostate dose, DP resulted in slightly higher TCP. Conclusion: Compared to homogeneous dose, DP maintains or marginally increases the TCP. Adaptive DP workflows could avoid target misses compared to conventional workflows.